(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents the design and simulation of broadband microstrip patch antenna using High Frequency Structure Simulator (HFSS).The two different configuration of broadband microstrip patch antenna, rectangular patch antenna & circular patch antenna are analyzed. The performance of designed antennas are analyzed in terms of return loss and gain. The substrate used in these two configurations is RT Duroid having dielectric constant 2.2.The result calculated is return loss of rectangular patch & C slot rectangular patch are -10.768 db& -13.4457db and gain of rectangular patch & C shape patch are 5.6197db& 5.7457db respectively. The calculated result for return loss of circular patch & C slot circular patch are -27.7852 db& -32.4685 db and gain of circular patch & C shape patch are 11.0708 db& 11.1834db respectively.